Детский остров: [стихи и сказка] / Саша Черный ; художник В. Власов - Черный Саша (Библиотека школьника, 2014)
Экземпляры: ф.7 (20190103) / Инвентарный номер: 59046 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Ч-49 / ГРНТИ: 17.82.93 / ББК: 84(2Роc=Рус)6